A cross-sectional household analysis of household consumption patterns : an indirect approach to identify the possible factors of personal bankruptcy - Toh, Siaw Mien; Rusmawati Said (Penerbit Universiti Kebangsaan Malaysia, 2018)
Although the standard of living has consistently improved, personal bankruptcy remains an uncommon issue in Malaysia. This paper investigates the relationship between consumption patterns and income of Malaysians by examining income elasticity using the Engel curve. Data were collected from the Household Expenditure Surveys of 2004, 2009, and 2014 and analysed using ordinary least square regression and the Working-Leser model. The results showed that out of 12 expenditure components, three were found to be necessity goods: food and non-alcoholic beverages, clothing and footwear, and housing and utility. It was found that households led by youths spent more on luxury goods compared to those led by heads aged 40 and above. Males, Bumiputeras, and households living in urban areas spent more on luxury goods. Tobacco, alcoholic beverages, hotels, private education, and private healthcare were considered as luxury goods for Malaysian households. This study suggests that the public, especially the younger generation, should be exposed more to the knowledge and awareness of debts, bankruptcy and lifestyles.